In Situ Absorption in Rat Intestinal Tract of Solid Dispersion of Annonaceous Acetogenins - Yun-Jie Dang; Han-Zhou Feng; Limei Zhang; Chun-Hui Hu; Chun-Yan Zhu (Gastroenterology Research and Practice)
Isolated from Annona squamosa L, Annonaceous acetogenins (ACGs) exhibit a broad range of biological properties yet absorbed badly due to the low solubility. Solid dispersion in polyethylene glycol 4000 (PEG 4000) has been developed to increase the solubility and oral absorption of ACGs. The formulation of ACGS-solid dispersion was optimized by a simplex lattice experiment design and carried out by a solvent-fusion method. We studied the absorption property of ACGs in rat’s intestine, which showed there was a good absorption and uptake percentages with solid dispersion. The study on uptake percentage in different regions of rat’s intestine attested that the duodenum had the best permeability, followed by jejunum, ileum, and colon in order with no significant differences. So the paper drew the conclusion that solid dispersion could improve the solubility and oral absorption of annonaceous acetogenins.